PERAN KEPALA DESA DALAM MENINGKATKAN PEMBANGUNAN DESA DI DESA BATURSARI KECAMATAN MRANGGEN KABUPATEN DEMAK - Hanggoro Prabowo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
The Villager's chief is a leader for village development based on the poling of Village Advisory Board (Badan Permusyawarahan Desa) to arrange and manage for society interest according to historical and customary legalized and respected for Indonesian Government. The Villager's chief as a motivator on development has purpose to improve the village society welfare, to rapid an advance and four village economic activity, and village industrialization.The village development is a process of ability improvement for villager to manage social emironment to catch their social welfare in the consequence for the management.